Changing Forms of Ownership in a Democratic Corporatist Media System — How Digitalization Leads to Less Transparency and the Risk of Media Capture - Mark Blach-Ørsten; Ida Willig; Mads Kæmsgaard; Rasmus Burkal (Comunicação e Sociedade)
Digitalization has led to a crisis in news media and an upheaval in media ownership. A research concern has been that the motives driving media owners will shift from financial and public service to overtly political and ideological. The term “media capture” has been suggested to describe how various interests may take control over news media outlets. This paper adds to the study of digitalization and media ownership in three ways. First, our analysis is based on new analytical parameters developed as part of the Euromedia Ownership Monitor. Second, we compare types of ownership across legacy news media and digital news media, as each media type runs a different risk regarding capture. Third, we focus on ownership transparency, especially that of beneficial owners. Our case study is Denmark, which is part of the democratic corporatist media system and, based on international ratings, is one of the most democratic and transparent media systems in Europe. We find that private legacy news media is mostly owned by nonprofit foundations, while legacy public service news media is owned by the State or is listed as self-owned. Regarding new digital news media, we find different ownership forms. However, only new digital news media have ownership by a sole proprietor. Regarding transparency, we find the transparency of direct and beneficial owners is more accessible in legacy news media than in new, digital news media. We find no tradition for publishing “natural persons” possible affiliations to either political or other commercial interests. This seems especially relevant, as new digital news media outlets, unlike legacy media, sometimes are owned and funded by private investors, whose main business interests lie outside the news media and whose motives for owning a news media may differ from traditional ownership thus leading to a risk of media capture by ownership.